Wells Gas Hydrates Formation Analysis and Prevention Methods - Liashenko, Anna; Melnikov, Oleksandr; Petrash, Ruslan; Petrash, Oleksandr (International Journal of Engineering and Technology, 2018)
The article deals with laws of occurrence of gas hydrates in mining wells and prevention of their formation. The basic calculations for determining temperature regimes in wells have been described. The basic methods of struggle against hydrated deposits in wells have been demonstrated. The detailed description of hydrates occurrence causes is presented along with methods of its prevention from a technological perspective. This paper provides data on the techniques used for production string clearing from hydrate plagues. The conditions necessary for hydrates formations are presented. The technological methods of hydrates removal from a tubing have been described.Â Â